REPRESENTASI EMANSIPASI WANITA DALAM BUDAYA JAWA PADA FILM KARTINI (2017) - Ayudia Putri, Rakhma; Rahardjo, Turnomo; Lukmantoro, Triyono (Interaksi Online, 2024)
The dissemination of values brought by films as mass media can influence society in constructing ideologies. In media ecology theory, media are considered more than just channels for message transmission; the inherent nature of the medium can be key to a social impact. This includes how various gender aspects regarding the portrayal of women's roles in films can affect societal perspectives and ideologies. "Kartini" (2017) is a biopic depicting the life journey of R.A. Kartini, a national female figure originating from Java who pioneered the women's emancipation movement in Indonesia. This research examines how the representation of women's emancipation is depicted through symbols in the film "Kartini" (2017) and how gender relations occur in feudal Java. This study employs qualitative descriptive research focusing on how Javanese culture can influence gender relations and power dynamics. Representation is conducted using John Fiske's semiotic analysis method, The Codes of Television, which examines the unit of analysis through three levels of social codes: reality, representation, and ideology. The research findings reveal that the representation of women's emancipation struggle in the film "Kartini" (2017) depicts women's roles as agents of resistance, challenging cultural norms and patriarchal ideologies that limit women's mobility within the entrenched patriarchy of Javanese culture. Patriarchy, through Javanese cultural traditions and values, legitimizes the subordination of women, thus necessitating emancipation movements to achieve physical, intellectual, and social liberation as a form of resistance against patriarchal hegemony. The representation of women's emancipation in the film "Kartini" (2017) illustrates how contradictions and negotiations are undertaken by women to drive social change and achieve gender equality.